2015
DOI: 10.1890/15-0030.1
|View full text |Cite
|
Sign up to set email alerts
|

Warming reinforces nonconsumptive predator effects on prey growth, physiology, and body stoichiometry

Abstract: While nonconsumptive effects of predators may strongly affect prey populations, little is known how future warming will modulate these effects. Such information would be especially relevant with regard to prey physiology and resulting changes in prey stoichiometry. We investigated in Enallagma cyathigerum damselfly larvae the effects of a 4°C warming (20°C vs. 24°C) and predation risk on growth rate, physiology and body stoichiometry, for the first time including all key mechanisms suggested by the general str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 61 publications
5
46
0
Order By: Relevance
“…While several recent studies found both stressors to interact (e.g. Touchon & Warkentin ; Culler, McPeek & Ayres ; Miller, Matassa & Trussell ; Janssens, Van Dievel & Stoks ), Chu et al . () showed no significant overlap in the transcriptomic responses to predation risk and thermal stress in the snail Nucella lapillus , indicating both stressors may impose distinct and potentially additive challenges.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While several recent studies found both stressors to interact (e.g. Touchon & Warkentin ; Culler, McPeek & Ayres ; Miller, Matassa & Trussell ; Janssens, Van Dievel & Stoks ), Chu et al . () showed no significant overlap in the transcriptomic responses to predation risk and thermal stress in the snail Nucella lapillus , indicating both stressors may impose distinct and potentially additive challenges.…”
Section: Discussionmentioning
confidence: 97%
“…They claimed this was because predator‐induced increases of C‐rich sugars were accompanied by increases in N‐rich proteins due to the increased production of tail muscles. Notably, the few studies that showed the predicted increase in body C : N under the GSP, either did not explicitly test for the assumed underlying GSP mechanisms (Hawlena & Schmitz ) or demonstrated the pattern could not be explained by GSP mechanisms (Janssens, Van Dievel & Stoks ). Taken together, this suggests that while predation risk can indeed affect the C : N ratio of the prey, a more general mechanistic framework is needed that reconciles the contrasting patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies experimentally examining the interplay between temperature and predation risk have provided mixed support for the original idea that rising temperature should exacerbate predation stress causing prey to consume more C (Jansens et al, 2015;Kirschman et al, 2016;Van Dievel et al, 2016;Zhang et al, 2016). These studies used 2 × 2 factorial designs that crossed a temperature treatment with a perceived predation risk treatment.…”
Section: Implications For Studies On the Stoichiometry Of Predation Smentioning
confidence: 99%
“…These shifts in nutrient intake should also be reflected in body element stoichiometry, with stressed prey having higher carbon [C]:nitrogen [N] ratios than non-stressed prey (Hawlena and Schmitz, 2010a). Some experiments have shown that such shifts in nutrient intake and body stoichiometry can indeed occur between conditions with and without perceived predation risk (McPeek et al, 2001;Hawlena and Schmitz, 2010b;Jansens et al, 2015). Other experiments have, however, shown that the predicted responses do not occur (Costello and Michel, 2013;Dalton and Flecker, 2014;Kaplan et al, 2014;Guariento et al, 2015;Kirschman et al, 2016;Van Dievel et al, 2016;Zhang et al, 2016), thereby calling into question the generality of the predicted stress response.…”
Section: Introductionmentioning
confidence: 99%
“…Prey can also allocate resources to develop and support new defense morphologies (e.g., larger tail muscles, and shell or exoskeleton fortifications; Tollrian and Harvell, 1999). Both physiological and morphological defenses can alter the nutritional composition of prey body and waste materials (e.g., Hawlena and Schmitz, 2010a;Dalton and Flecker, 2014;Guariento et al, 2015;Janssens et al, 2015). When decomposed, carcasses and waste materials of stressed animals may affect the SFW differently from those of non-stressed prey (Fig.…”
Section: Main Textmentioning
confidence: 99%